Integrating Occupational Health and Safety (OHS) into Chemical Laboratory Learning: A Mixed-Method Study on Students’ Safety Awareness and Practices - Hassan Abdullahi Dachia; Jairus Bulimo Khamali; FKR Kumabia (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze students’ occupational health and safety (OHS) awareness and practices in chemical laboratory learning and to evaluate the effectiveness of integrating OHS principles into laboratory instruction to reduce safety risks and improve compliance. Methodology: This study employed a mixed-method approach using structured questionnaires, observation sheets, semi-structured interviews, and document analysis. Data were collected from undergraduate chemistry students. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through thematic analysis. Job Safety Analysis (JSA) was applied as a risk assessment tool. Main Findings: The results showed that 78% of students received safety training, but only 34% could identify hazard symbols correctly. Compliance with safety practices was low, including fume hood usage (25%) and chemical waste disposal (10%). JSA results indicated that 19% of laboratory activities were categorized as high to extreme risk levels. Novelty/Originality of this study: This study provides a novel integration of Job Safety Analysis (JSA) into chemical laboratory learning to systematically identify risks and improve safety practices. It also offers an evidence-based approach for embedding OHS into the curriculum, contributing to the development of a proactive laboratory safety culture.